Strategi Pembelajaran Mandiri dalam Memusatkan Perhatian Siswa Pada Mata Pelajaran Fiqih untuk Meningkatkan Prestasi Belajar (Studi di Madrasah Tsanawiyah Negeri 1 Pesisir Selatan) - Fithidayati Fithidayati; Isman Efendi Limbong (UMSU, 2022)
The purpose of this study was to determine the implementation of independent learning strategies in focusing students' attention on learning fiqh at Madrasah Tsanawiyah Negeri 1 Pesisir Selatan. The approach used in this study is to use a descriptive qualitative approach. The data analysis technique used is data reduction, data display and data simplification. The results or findings obtained from this research study are that independent learning strategies in focusing students' attention on Fiqh subjects at Madrasah Tsanawiyah Negeri 1 Pesisir Selatan are in the form of; (a) Creating a more lively and enjoyable learning atmosphere; (b) Creating students' personalities including tolerance, democratic attitudes, critical thinking skills and creating students' ability to be patient; (c) Applying questioning skills; (d) Use language that is polite, respectful and in a soft tone of voice; (e) Strategy in providing reinforcement; and (f) Carrying out method variations.